Development and validation of the attitude towards Surrogacy Scale in a polish sample - Karolina Lutkiewicz; Łucja Bieleninik; Paweł Jurek; Mariola Bidzan (BMC, 2023)
Abstract Background Surrogacy is one of the options in reproductive medicine that raises a lot of ethical, legal and psychological controversy. Surveying attitudes toward surrogacy plays an important role in building awareness of this phenomenon in the society, which may help eliminate its stigma. In this study authors aimed to develop and validate a scale to assess the attitudes towards surrogacy. Methods In this study cross-sectional design was implemented. Development process of the Attitude towards Surrogacy Scale (ATSS) included items development based on literature reviews, other existing questionnaires, confirmatory factor analysis (CFA), and reliability analysis using internal consistence coefficients. A pilot study using adult members of the public was conducted after consultation with the Expert Advisory Panel Board. The final survey, which was used in this study, consisted of 24 items, which were organized into the four subscales: general opinion on surrogacy and its social context (7 items), financing and legalizing surrogacy (8 items), the acceptance of surrogacy (4 items), and attitudes towards the intended parents and children born through surrogacy (5 items). 442 individuals participated in this study. Results The final version of Attitude towards Surrogacy Scale (ATSS) consists of 15 items, grouped in three subscales. Final version of the ATSS showed that the three-factor model indicated an acceptable model fit: Chi-square = 320.46, p < 0.01, df = 87, CFI = 0.94, TLI = 0.92, RMSEA = 0.078 (90% C.I.: 0.070-0.086), SRMR = 0.040 Reliability was assessed by calculating the McDonald's omega that ranged from 0.74 for the Surrogacy ethical context subscale to 0.94 for the overall ATSS score. Conclusion ATSS was developed to measure general attitude toward surrogacy with satisfying psychometric properties. The analysis of socio-demographic variables with ATSS showed that the most significant predictor of the general attitude towards surrogacy, and three aspects of surrogacy was being a religious person (profess a Catholic religion or profess another religion).